A Neural Network Based Speed Control of a Dual Star Induction Motor - Meliani Bouziane; Meroufel Abdelkader (International Journal of Electrical and Computer Engineering (IJECE), 2014)
This paper propose the use of artificial neural networks to control the speed of a Double Star Induction Motor drives fed by a two matrix converter using Venturini modulation algorithm, The advent of the field oriented with modern speed control technique has partially solved DSIM control problems because it is sensitive to drive parameter variations and performance may deteriorate if conventional controllers are used. Neural network based controller is considered as potential candidates for such an application. In this work the simulations results are provided to evaluate performance of the proposed control strategy.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6343